CHORY TERMINALNIE I JEGO RODZINA - Górecki, Mirosław (Wydział Prawa i Administracji UAM, 1999)
The increasing number of men falling ill with cancer and the number of decease because of this illness poses more and more strongly the problem of a care of terminally-ill persons. The medicine focuses mainly on curing an ill patient and has neglected the function of care of a dying person. The hospice care offers a help to a person in agony, dying in suffering and loneliness. The article presents the situation of a hospice patient and of his family which is the point of reference for the role and activities of the hospice officers and demonstrates how is this help being appreciated by persons under care. The Author has made his research study in the period 1995 - 1997; the study referred to the ills, their families, hospice volunteers and officers of palliative care, and - finally - to hospice and palliative centres. In particular - the article discusses such issues as qualifying criteria for a hospice patient, methods of getting in contact with the ill, his reactions to his own state of the health and also - the quality itself of social relations as formed before the illness and then - under its influence. 10
A TERMINALLY-ILL MAN AND HIS FAMILY